Desempenho da mesa termogradiente e avaliação de genótipos de arroz tolerante à baixa temperatura - Freitas, Demócrito Amorim Chiesa (2005)
To evaluate the performance of a thermogradient table in the maintenance of different temperatures and ranking genotypes of rice according to its germination capacity at law temperature. For this procedure it was used a thermogradient table of the Seed Analysis Laboratory of Faculdade de Agronomia Eliseu Maciel of Universidade Federal de Pelotas RS, manufactured in Brazil. Forty genotypes of rice were used, ranking through the determination of the percentage and speed of the germination in four temperatures (10ºC, 13ºC, 16ºC and 19ºC) and the behavior of the genotypes in relation to the stress at low temperature. It was concluded that: a) there is great variability among genotypes of rice, as for the tolerance of the germination in low temperature, with emphasis in the following varieties: Colonial, IRGA 418, BR IRGA 411 and EEA 406. b) There are genotypes of rice that present more than 50% of germination in temperature of 10ºC up to two weeks after the sowing. c) The thermogradient table is an equipment capable of maintaining stable temperature in each ruler, with a maximum variation of one degree Celsius. d) The thermogradient table allows to manitor the performance of seeds of genotypes of rice, in different temperatures, simultaneously